Alteration of the Optoelectronic Properties of CuInS2 Quantum Dots via Colloidal Annealing - Dehm, Katharina; Zanetti, Alberto; Fett, Bastian; Mauritz, Vincent; Hamburger, Robert C.; Langford, Daniel; Guldi, Dirk Michael; Young, Elizabeth R.; Mandel, Karl; Crisp, Ryan (Crystal Growth and Design, 2024)
Colloidal semiconductor quantum dots (QDs) have tunable optoelectronic properties, thereby making them interesting materials for applications involving light-matter interactions. However, crystallographic and surface defects greatly impair their potential performance in devices. Herein, we present a straightforward approach to improve the quality of copper indium disulfide (CuInS2) QDs by adjusting the parameters of the colloidal synthesis. By the introduction of prolonged heating times after the nanocrystal growth has already gone to completion, defect states are partially removed. This “colloidal annealing” for varying time spans (from 5 up to 90 min) with longer annealing times correlating with a decreased ratio of emission from defect states compared to band edge emission, results in enhanced color purity. At shorter annealing times, the defects removed are mainly structural, indicated by the transition from mixed crystal phases to an almost phase-pure material. At longer annealing times, further improvements are linked to surface defect removal. Findings from transient absorption spectroscopy further confirm this trend by revealing a decrease in the intensity of a photoinduced absorption feature associated with sub-band gap states compared to the band edge bleach signal. These findings highlight the applicability of colloidal annealing as a straightforward strategy for direct material optimization during colloidal synthesis.<br

Colloidal nanocrystal synthesis of alkaline earth metal sulfides for solution-processed solar cell contact layers - Mauritz, Vincent; Dehm, Katharina; Hager, Simon; Crisp, Ryan (Zeitschrift fur Kristallographie - Crystalline Materials, 2023)

Colloidal organometallic synthesis of solution-processable barium titanate nanoparticles for nanoelectronic applications - Linke, Lara Kim; Dehm, Katharina; Gubanov, Kirill; Fink, Rainer; Szyja, Bartłomiej M.; Crisp, Ryan (Nanoscale, 2025)
Perovskite oxides like barium titanate (BaTiO3) exhibit desirable properties: notably high dielectric constants, piezoelectricity, and ferroelectricity, thereby enabling more advanced electronic devices and actuators. There are numerous synthesis procedures for BaTiO3, among which, nanoparticle syntheses are versatile and well-studied. However, colloidal organometallic synthesis is less commonly employed for this material despite offering processing advantages like facile compositional control and customizable surface chemistry. Here, an organometallic synthesis route is explored to produce colloidally stable BaTiO3 nanoparticles with oleyl alkoxide ligands. Subsequently, we further develop ligand exchange procedures with X-type ligands using KOH and oxalic acid to produce colloidal inks applicable for solution-processed nanocrystalline films for dielectrics in devices for which there is still a need for better nanoscale control. The BaTiO3 nanoparticles and films were characterized using X-ray diffraction (XRD), scanning transmission electron microscopy (STEM), energy-dispersive X-ray spectroscopy (EDS), Fourier-transform infrared spectroscopy (FT-IR), atomic force microscopy (AFM), Kelvin probe force microscopy (KPFM), and density functional theory (DFT), to understand their properties and to develop processes for device applications.
CRIS-Team Scopus Importer:2025-03-28

Monolithic Two-Terminal Tandem Solar Cells Using Sb2S3 and Solution-Processed PbS Quantum Dots Achieving an Open-Circuit Potential beyond 1.1 V - Kern, Selina; Yi, Gyusang; Büttner, Pascal; Scheler, Florian; Tran, Minh Hoa; Korenko, Sofia; Dehm, Katharina; Kundrata, Ivan; Zahl, Achim; Albrecht, Steve; Bachmann, Julien; Crisp, Ryan (ACS Applied Materials and Interfaces, 2024)
Multijunction solar cells have the prospect of a greater theoretical efficiency limit than single-junction solar cells by minimizing the transmissive and thermalization losses a single absorber material has. In solar cell applications, Sb2S3 is considered an attractive absorber due to its elemental abundance, stability, and high absorption coefficient in the visible range of the solar spectrum, yet with a band gap of 1.7 eV, it is transmissive for near-IR and IR photons. Using it as the top cell (the cell where light is first incident) in a two-terminal tandem architecture in combination with a bottom cell (the cell where light arrives second) of PbS quantum dots (QDs), which have an adjustable band gap suitable for absorbing longer wavelengths, is a promising approach to harvest the solar spectrum more effectively. In this work, these two subcells are monolithically fabricated and connected in series by a poly(3,4-ethylene-dioxythiophene) polystyrene sulfonate (PEDOT:PSS)-ZnO tunnel junction as the recombination layer. We explore the surface morphology of ZnO QD films with different spin-coating conditions, which serve as the PbS QD cell’s electron transport material. Furthermore, we examine the differences in photogenerated current upon varying the PbS QD absorber layer thickness and the electrical and optical characteristics of the tandem with respect to the stand-alone reference cells. This tandem architecture demonstrates an extended spectral response into the IR with an open-circuit potential exceeding 1.1 V and a power conversion efficiency of 5.6%, which is greater than that of each single-junction cell.
CRIS-Team Scopus Importer:2024-03-29
Keywords: antimony sulfide; atomic layer deposition; chalcogenide solar cells; lead sulfide; mapping ellipsometry; multijunction; nanocrystals; recombination layer

Sustainable Repellent Coatings Based on Renewable Drying and Nondrying Oils - Dehm, Katharina; Walter, Teresa; Weichselgartner, Matthias; Crisp, Ryan; Wommer, Kirsten; Aust, Martin; Vogel, Nicolas (Advanced Materials Interfaces, 2022)

Transparent TiO2 nanotubes supporting silver sulfide for photoelectrochemical water splitting - Lipińska, Wiktoria; Wolff, Stefania; Dehm, Katharina; Hager, Simon; Gumieniak, Justyna; Kramek, Agnieszka; Crisp, Ryan; Coy, Emerson; Grochowska, Katarzyna; Siuzdak, Katarzyna (Nanoscale, 2024)
Differences between photoelectrochemical and electrochemical activity were thoroughly investigated for the oxygen evolution reaction mediated by Ag2S deposited on two types of ordered titania substrates. Titanium dioxide nanotubes were fabricated by anodization of magnetron sputtered Ti films on ITO-coated glass substrates or directly from Ti foil. Further, Ag2S deposition on the nanotubes was carried out using successive ionic layer adsorption and reaction, known as SILAR, with 5, 25, and 45 cycles performed. Two types of nanotubes, one on transparent the other on non-transparent substrates were compared regarding their geometry, structure, optical, and electrochemical properties. It was demonstrated that the composite of Ag2S grown on transparent nanotubes exhibits higher catalytic activity compared to Ag2S grown on the nanotubes formed on Ti foil. The results showed that transparent nanotubes after modification with Ag2S by 25 SILAR cycles exhibit ca. 3 times higher photocurrent under visible light illumination than non-transparent ones treated with the same number of cycles. Furthermore, transparent nanotubes after 45 SILAR cycles of Ag2S exhibit enhanced activity towards oxygen evolution reaction with 9.3 mA cm−2 at 1.1 V vs. Ag/AgCl/0.1 M KCl which is six times higher than titania alone on Ti foil.
CRIS-Team Scopus Importer:2024-08-09